2004
DOI: 10.1038/sj.onc.1207482
|View full text |Cite
|
Sign up to set email alerts
|

Cdk2-dependent phosphorylation of the NF-Y transcription factor is essential for the expression of the cell cycle-regulatory genes and cell cycle G1/S and G2/M transitions

Abstract: We previously reported that cdk2 phosphorylates two serine residues near the DNA-binding domain of the YA subunit of NF-Y transcription factor and this phosphorylation is essential for DNA binding of NF-Y. In this study, we examined the effects of a phosphorylationdeficient mutant form of YA, YA-aa, in which the two serine residues are replaced with alanine, on the cell cycle and expression of the NF-Y target genes. Transient transfection assays show that YA-aa inhibits transcription from the NF-Y target promo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
55
0
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 62 publications
(62 citation statements)
references
References 29 publications
4
55
0
1
Order By: Relevance
“…immunoprecipitation (IP)-kinase assay showed that while both Cdk2 and Cdc2 were not detected in HCT116 cells, both kinases remain unchanged in p53-and p21-knockout cells following PTX-2 treatment (Figure 1c). Therefore, inactivation of Cdk2 and Cdc2 kinases in p53-positive cells should be due to p21-mediated inhibition, supporting our previous report that p21-mediated Cdk2 inhibition lead to Cdc2 inactivation (Yun et al, 2003;Chae et al, 2004).…”
Section: Actin Inhibitors Activate P53-signaling Pathwaysupporting
confidence: 88%
See 1 more Smart Citation
“…immunoprecipitation (IP)-kinase assay showed that while both Cdk2 and Cdc2 were not detected in HCT116 cells, both kinases remain unchanged in p53-and p21-knockout cells following PTX-2 treatment (Figure 1c). Therefore, inactivation of Cdk2 and Cdc2 kinases in p53-positive cells should be due to p21-mediated inhibition, supporting our previous report that p21-mediated Cdk2 inhibition lead to Cdc2 inactivation (Yun et al, 2003;Chae et al, 2004).…”
Section: Actin Inhibitors Activate P53-signaling Pathwaysupporting
confidence: 88%
“…To select stable cell lines expressing Bcl-x L , we transfected p53-knockout cells with pPuro-Bcl-x L . A recombinant adenovirus encoding Cdk2dn was constructed as previously described (Chae et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…The crucial role of cdk2 activity is known to induce the expression of cell cycle-regulatory genes, thus leading to cell cycle progression (Chae et al, 2004;Yu et al, 2004). Therefore, inhibiting the phosphorylation ability of this kinase with the Spa310 small molecule is likely to induce cell cycle arrest.…”
Section: Spa310 Triggers Suppression Of Cell Growth Observed By Colonmentioning
confidence: 99%
“…p21 induction causes subsequent arrest in the G1 phase by binding to cyclin E-and A-associated cdk2 complexes (Gu et al, 1993;Harper et al, 1993;Xiong et al, 1993). Recently, we reported that p53 and p21 also inactivate cyclin B-associated cdc2 kinase by repressing the transcription of cyclin B, cdc2, and cdc25C genes, and that this repression is mediated by the cdk2-dependent phosphorylation of NF-Y (Park et al, 2000;Yun et al, 2003;Chae et al, 2004). Other recent studies have described additional p53 target genes that are likely to activate cell cycle checkpoints and induce apoptosis (Vousden and Lu, 2002).…”
Section: Introductionmentioning
confidence: 99%